2017
DOI: 10.1111/bju.13968
|View full text |Cite
|
Sign up to set email alerts
|

Impact of warm ischaemia time on postoperative renal function after partial nephrectomy for clinical T1 renal cell carcinoma: a propensity score‐matched study

Abstract: ObjectivesTo analyse the effect of prolonged warm ischaemia time (WIT) on long-term renal function after partial nephrectomy (PN), as controversy still exists as to whether prolonged WIT adversely affects the incidence of chronic kidney disease (CKD) after PN. Patients and MethodsWe reviewed data from 1816 patients who underwent PN for a clinical T1 renal tumour. The propensity scores for prolonged WIT were calculated with the shorter WIT group (<30 min) matched to the longer WIT group (≥30 min) in a 2:1 ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
(26 reference statements)
3
27
0
Order By: Relevance
“…We defined postoperative renal impairment as a ≥25% ultimate eGFR decrease from preoperative eGFR, which was consistent with previous studies. 5,17 The impact of AKI on renal impairment was evaluated. A temporary ≥25% eGFR decrease, which recovered thereafter, was not considered renal impairment.…”
Section: Intermediate-term Change In Renal Function After Clampless Pnmentioning
confidence: 99%
“…We defined postoperative renal impairment as a ≥25% ultimate eGFR decrease from preoperative eGFR, which was consistent with previous studies. 5,17 The impact of AKI on renal impairment was evaluated. A temporary ≥25% eGFR decrease, which recovered thereafter, was not considered renal impairment.…”
Section: Intermediate-term Change In Renal Function After Clampless Pnmentioning
confidence: 99%
“…Tumour size and renal function are vital determinants of suitability for PN . This publication clearly demonstrates that although large tumour size equated with prolonged clamp time, this was not the sole determinant of impaired long‐term renal function.…”
mentioning
confidence: 78%
“…In the latest edition of the BJUI , Lee et al. have revisited the question of defining the ideal limit of warm ischaemia time (WIT) and its impact on postoperative renal function in patients undergoing partial nephrectomy (PN).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that medical CKD rather than surgically induced CKD is a more important driver of postoperative renal function [7]. Propensity-matched data for almost 2000 patients comparing the effects of shorter and longer WIT (<30 vs >30 min) revealed no significant differences between the groups and confirmed that prolonged WIT is not associated with CKD or renal function deterioration [8]. It is clear from these studies that it is overly simplistic to consider a single IT cutoff as a dichotomous marker for renal injury.…”
Section: Evidence Synthesismentioning
confidence: 90%